Annual and semi-annual variations of electron density in the topside ionosphere observed by CSES - Zhu, Keying; Yan, Rui; Xiong, Chao; Zheng, Lin; Zhima, Zeren; Shen, Xuhui; Liu, Dapeng; Guan, Yibing; Liu, Chao; Xu, Song; Lv, Fangxian; Guo, Feng; et al. (Frontiers in Earth Science, 2023)
In this paper, based on the observations from Langmuir probe (LAP) onboard the China Seismo Electromagnetic Satellite (CSES), four years electron density (Ne) data measured at 02:00 and 14:00 local time (LT) have been analyzed, to investigate the annual/semi-annual variation of Ne in the topside ionosphere. Results indicated that the Ne exhibits an amplification-linear-saturation with P10.7 in the daytime, however roughly linear in the nighttime. And both of them show a strong annual/semi-annual variation of CSES Ne at around 500 km, which showed dominant frequencies of 177 days and 354 days. By morphological analysis and FFT decomposition, the annual components of longitude-averaged Ne dominate at most magnetic latitudes with maxima around the June solstices in the northern hemisphere and the December solstice in the southern hemisphere (expect for the norther hemisphere in the nighttime), while the semi-annual variation dominate at the magnetic equator and low magnetic latitude (Mlat) with two maximums at equinoxes. The Ne dominant period is characterized by a transition from semi-annual variation at the equator and low Mlat regions to annual variation at the middle Mlat region. The annual/semi-annual variation of Ne observed by CSES satellite show a consistent performance with previous studies, and have complemented the ionospheric characteristics at 500 km altitude, especially in the nighttime.